Assessment of the initial state of two reserves, Micro áreas Ecoturísticas Litorales (MAEL), in Gran Canaria, Canary Islands - Vidal López, Javier Rodrigo (2015)
The establishment of 'Micro áreas ecoturísticas litorales' (MAELs) is a new strategy of marine conservation and management, based on a bottom-up governance strategy. In this study, we assessed the initial state ('state 0') of two MAELs at Gran Canaria Island (Canary Islands): 'El Cabrón' and 'Las Canteras', located in the east and in north-east coast of Gran Canaria Island, respectively. Specifically, we evaluated differences in the abundance and biomass of target fish species between inside (MAELI) and outside (MAELO) these two proposed reserves; five commercially-targeted fish species were selected: the parrotfish, Sparisoma cretense, the white sea-bream, Diplodus sargus cadenati, the common two-banded sea-bream, Diplodus vulgaris, the island grouper, Mycteroperca fusca, and salema, Sarpa salpa. Fish assemblages were sampled at 7 times within each management category in during summer and autumn of 2013. Univariate tests provided an overall moderate ‘reserve effect’ for the initial state of both MAELs. Mycteroperca fusca and Diplodus vulgaris showed greater abundances and biomasses, respectively, within the ‘El Cabrón’ MAELI compared to the adjacent MAELO. Sparisoma cretense, Diplodus sargus cadenati, Diplodus vulgaris and Sarpa salpa showed greater abundances and biomasses within the 'Las Canteras' MAELI compared to the adjacent MAELO. Furthermore, we tested whether taxonomic diversity (through calculation of the Shannon diversity index for the entire fish assemblage) may be a surrogate for the trophic and functional diversity of the fish assemblage to adequately support the capacity of MAMPs to preserve marine biodiversity. Our data suggested a neat link between them. "Micro áreas ecoturísticas litorales" (MAELs) es una nueva estrategia de gestión y conservación marina, basada en la estructura de decisión bottom-up. En este estudio, evaluamos el estado inicial ('estado 0') de dos MAELs en Gran Canaria (Islas Canarias). 'El Cabrón' y 'Las Canteras', localizadas en este y noreste de la isla de Gran Canaria, ...